PENANAMAN NILAI-NILAI DEMOKRASI DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SMP NEGERI 7 KOTA TERNATE - Abdullah, Jainudin; Yusuf, Mukhtar; Salong, Abjan (Universitas Khairun, 2024)
The purpose of this study is to analyze (1) how to instill democratic values in Civics learning at SMP Negeri 7 Kota Ternate. (2) What factors hinder the instillation of democratic values in Civics learning at SMP Negeri 7 Kota Ternate. The approach used in this study is qualitative. Data sources of School Principals, Curriculum affairs, Student affairs, Public Relations affairs, Civics teachers and students The results in this study show (1) The instillation of democratic values in Civics learning at SMP Negeri 7 Ternate City is the democratic value of tolerance, the democratic value of respecting differences, the value of open democracy in communicating, the value of confident democracy, the democratic value of responsibility, the democratic value of cooperation, the democratic value of togetherness and the democratic value of obedience. (2) What factors hinder the instillation of democratic values in Civics learning at SMP Negeri 7 Kota Ternate are factors from within the students themselves lack of motivation to learn Civics subjects, environmental influence factors also affect students' attitudes to learn Civics subjects, factors of lack of attention from parents of students studying at school and at home.